64 ASBESTOS-INDUCED INFLAMMATION AND FIBROSIS ARE REGULATED BY RAC1. (1st March 2007) - Tephly, L. A.; Dodd, A.; Thorne, P. S.; Glogauer, M.; Carter, A.
Abstract : The release of TNF-α by alveolar macrophages plays an integral role in the pathogenesis of the inflammatory response that occurs in the lungs of patients with asbestosis. In contrast to most stimuli, our data demonstrate that the p38 MAP kinase is a positive regulator and the ERK MAP kinase is a negative regulator of TNF-α production in response to asbestos stimulation. However, limited data are available on the upstream signaling pathways linking asbestos with TNF-α expression. The GTPase Rac1 is an upstream second messenger that plays an important role in inflammation. We found that TNF-α production is augmented in monocytes overexpressing Rac1. We hypothesized that Rac1 plays a pivotal role in differentially modulating MAP kinase activation and that this differential activation is critical for TNF-α gene expression in human monocytes stimulated with asbestos. We explored the role of Rac1 in regulating the activation of MAP kinases. Our data demonstrate that overexpression of Rac1 increased p38 activity and abolished ERK activity. In contrast, overexpression of a dominant negative Rac1 increased ERK and inhibited p38. To determine if Rac1 and differential MAP kinase activity had any biologic significance, we exposed wild-type and Rac1 null mice to asbestos. Wild-type mice had significantly more inflammatory cell infiltration and produced more TNF-α compared with Rac1 null mice. More importantly, wild-type mice developed interstitial fibrosis, whereas Rac1 null mice exposed to asbestos were no different from saline controls. In aggregate, these data suggest that Rac1 has a pivotal role in regulating MAP kinase activity and TNF-α gene expression in monocytes, and the absence of Rac1 in inflammatory cells is protective against the development of pulmonary fibrosis after asbestos exposure. ALA CI AWARD and VA MERIT.